HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN PROKRASTINASI AKADEMIK PADA MAHASISWA UMSIDA - Ghozali Rusyid Affandi; Ari Heryanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
This research is motivated by the existence of problems related to academic procrastination among students of Muhammadiyah University of Sidoarjo. Students have a tendency to leave or avoid their tasks and activities in the academic world intentionally, which makes it difficult to complete lectures on time. Students have feelings of dislike for the tasks they get, as well as feelings of fear of failure, fighting against control and difficulty in making decisions. The purpose of this study is to determine the relationship between peer social support and academic procrastination in students. This research method is quantitative correlation with a population of 10,006 students of Muhammadiyah University of Sidoarjo and used as a sample of 370 based on the Krejcie and Morgan table with a 5% error rate. The sample determination uses an accidental sampling technique. The variables in this study are peer social support and academic procrastination. Data collection in this study used a scale of peer social support and academic procrastination with a Likert scale model adopted from previous studies with a reliability value of 0.892 for the peer social support variable and 0.775 for the academic procrastination variable. Data analysis in this study used the Spearman Rho correlation test with the help of SPSS. The results showed that there was a negative relationship between peer social support and academic procrastination in students of the University of Muhammadiyah Sidoarjo, with a value of r = -0.334 with a significance value of p = 0.000 (p <0.05). The higher the peer social support, the lower the academic procrastination and vice versa.